Evaluation of plasma catestatin levels in patient with coronary slow flow - Topal, Dursun; Boyraz, Bedrettin; Akgümüş, Alkame; Peker, Tezcan; Yılmaz, Mustafa; Vatansever Ağca, Fahriye; Kanat, Selçuk; Aydın, Ömür; Aslan, Burhan (The European Research Journal, 2019)
﻿Objectives: Coronary slow flow (CSF) is characterized by delayed opasification of the coronary arteries in the absence of obstructive coronary disease. Catestatin has several cardiovasculer actions, in addition to diminihed sympato-adrenal flow. The study was to investigated associations between CSF and plasma catestatin levels. Method: This study included 45 CSF patients (37 male, mean age 48 ± 9.5 years) and 30 control individuals (24 male, mean age 48.4 ± 9 years). Coronary flow was quantified according to the TIMI (Thrombolysis in Myocardial Infarction) frame count method for coronary arteries. Serum catestatin levels taken from blood samples were measured by ELISA method. These parameters were compared between the groups. Results: When compared with to the control group the serum catestatin levels was found higher in the CSF group. In addition to this, mean platelet volume was also significantly higher in patients with coronary slow flow. Conclusions: Our study revealed that catestatin levels are increased in patients with CSF. Coronary slow flow that increased catecholaminergic sympathetic system activities seem to be among the reasons of endothelial dysfunction.